The Role of Communication Management in the Corporate Integration System Management of Industrial Enterprises - M. ZELISKO; T. M. KHALIMON; S. M. KHALIMON (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article presents the role and significance of communication management for the functioning of enterprises in a globalized, complex, and dynamic economic environment, which requires the implementation of new management approaches to ensure effective activity and increase competitiveness. The theoretical principles of communication management of enterprises are revealed, which ensures consistency of actions, timeliness of management decisions and adaptation to exogenous challenges and threats.From a historical point of view, communication management emerged as an approach to organizing information flows in the process of interaction between people involved in the economic activities of an enterprise and in communication with partners, clients and other market participants. Among scientists, there is no unity of views on the time of the formation of communication management as a separate branch of management knowledge. However, analyzing the evolution of management and communications, it is possible to conditionally distinguish several stages of development of this direction, reflecting the gradual professionalization of management of communication processes.Modern development trends and components of communication management in the system of enterprise management are identified, as decisive imperatives for achieving strategic goals of enterprises. The importance of integration processes and the introduction of integration forms of entrepreneurship in conditions of geopolitical and economic crisis phenomena is substantiated.The economic content and functions of corporate integration management of enterprises are characterized. The main functions of corporate integration management of industrial enterprises are: strategic planning, organization, motivation and development, coordination, information support, monitoring and control, as well as regulation and adaptation.Key technologies and approaches used in the field of corporate integration are presented. Priority areas of development of communication management in the corporate integration management system of enterprises are proposed.In the globalized world, the role of communications is constantly growing, becoming one of the determining factors in the formation of enterprise development strategies. Modern communications are no longer limited to the transmission of information or informing stakeholders. Their main purpose is to create opportunities for more active involvement of stakeholders in new business processes, transformation of channels and formats of interaction, and increasing the level of trust between participants in the communication environment. Such changes lead to a rethinking of the very essence of communication management as a strategic imperative for the development of corporate integration management of industrial enterprises, which ensures an increase in their competitiveness, forms reputational capital, and promotes sustainable business development in conditions of uncertainty.